Diode-seeded nanosecond Yb-doped fiber amplifier operating at the repetition rate up to 500 kHz - Świderski, Jacek; Zając, Andrzej; Skorczakowski, Marek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
The paper presents a laser system developed in MOFPA (Master Oscillator Fiber Power Amplifier) configuration. A pulsed single-mode laser diode operating at the wavelength of 1060-nm was used as a seed. An ytterbium-doped double-clad Large Mode Area fiber pumped by the radiation of 978-nm played a role of an active medium. The developed laser system generated a pulse train with duration ranging from about 11 ns to 200 ns at the repetition rate up to 500 kHz, regulated independently of the system gain. The maximum amplification of the fiber amplifier was 32 dB.
Optica Applicata, Vol. 38, 2008, nr 4, s. 669-676
Keywords: optyka; double-clad optical fiber; fiber amplifier; pulse generation